EVALUASI TARI PIRING TAMBUA TASA DI SANGGAR RUMAH CHIKA PEKANBARU DALAM KAJIAN KRITIK SENI - Ulya, Latifa Zatil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This paper aims to evaluate Tambua Tasa plate dance in Rumah Chika Studio Pekanbaru. The method used in this research uses qualitative methods that are descriptive analysis. Data collection wa s carried out in three stages, namely observation, interviews, and documentation. The findings obtained are that the absence of motion processing as in the science of choreography in this plate dance is a form of choreographer's efforts in making dance works quickly where the dance is made for entertainment and for commercial purposes. However, it would be better if the mention of the source of the Tambua Tasa plate dance is sounded in the narration that is usually spoken by the announcer in the event where this plate dance is performed, or made in the caption on the social media upload belonging to the Rumah Chika studio, so that this will provide a sense of mutual respect between fellow dance artists.